KEMAMPUAN KEUANGAN DAERAH DALAM MELAKUKAN PINJAMAN SEBAGAI ALTERNATIF SUMBER PENDANAAN PEMBANGUNAN DI KABUPATEN LANDAK - M A R D I M O, B61109057 (Jurnal Ekonomi Daerah (JEDA), 2015)
Abstract local government district otherwise allow it to make loans because it has a number DSCR (Debt to Service Coverage Ratio) greater than 2.5. Likewise, the maximum loan limit (BMP) is the cumulative number of principal areas that must be paid does not exceed 75% (seventy five percent) of the total revenue in the previous budget year. The basic concept of area borrowing in PP 54/2005 and PP 30/2011 on the principle derived from the Law 33/2004 on Fiscal Balance between Central and Regional Government. The law states that in the implementation of regional autonomy and fiscal decentralization, to provide an alternative source of financing for local governments to accelerate regional economic growth and improve service to the public, the local government may apply for loans. Keywords: regional lending, financial capability Â